MALE RATS PLAY A REPEATED DONATION GAME - Li, Grace (Physiol Behav, 2017)
While previous studies have demonstrated direct and generalized reciprocity in female Norway rats (Rutte and Taborsky, 2008), the present study determined if unrelated male laboratory rats respond on behalf of a partner in an iterated sequential game. Pairs of rats worked for food reward in an operant chamber, where participants alternated as Donor and Responder in successive trials. In each trial, the Donor chose between variable and constant reward levers, where the constant reward lever delivered 1 pellet, and the variable reward lever triggered insertion of Responder lever(s); the Donor received 2 pellets when the Responder made any response. In forced-choice constant (FC) trials, the Responder also received 1 pellet for responding on the constant reward lever. In forced-choice variable (FV) trials, the Responder received no pellets for responding on the variable reward lever. In free-choice (FR) trials, the Responder chose between constant (1 pellet) and variable reward levers (0 pellets). With their cagemate, rats earned 61.4±2.0 pellets (64.0±2.1% of 96 possible pellets). As Donor in FC trials, rats preferred the variable reward lever, and the Responder responded frequently. In FV trials, Donor preference for the variable reward lever declined as Responder lever responses decreased. In FR trials, rats alternated responding on variable and constant reward levers as Donor and Responder, respectively. When paired with a new partner, there was no effect on Donor responses, but responses by the Responder decreased in the FV block. Similar effects were observed when paired with a maximally-cooperative stooge. Importantly, rats did not adjust their behavior as Donor to receive more pellets. Results suggest that unrelated male rats will work on behalf of a partner, and that their behavior is sensitive to familiarity, and to cooperative responses by their partner.